Self-inclusion of proline-functionalised calix[4]arene leads to hydrogelation - Goh, Ching; Becker, Thomas; Brown, David; Skelton, B.; Jones, Franca; Mocerino, Mauro; Ogden, Mark (The Royal Society of Chemistry, 2011)
Solution-phase and solid-state structural studies indicate that the remarkable hydrogelation properties of a proline-functionalised calix[4]arene emerge as a result of extended helical structures formed via inclusion of a proline moiety in a neighbouring calixarene cavity.